PEMBERDAYAAN KOPERASI BERBASIS ANGGOTA - Harini, Harini (MIIPS, 2010)
Basically co-operative member of empowerment is the responsibility of the Board ofDirectors, as in the degree of UU. No.25 Th 1992, pasal 23, ayat 2a, that education for themembers in every co-op instution is responsibility of the board upon the mandate given by theÂ highest authority General Assembly (Rapat Anggota /RAT).Empowerment of co-operatives emerged as a result of human weakness on the onehand, while on the other hand, demands appreciation of the values and principles of cooperative experience laden ideal , invites potential problems objectively. The goal ofempowerment of co-operatives to co-operative is able to realize what was to become his goal.Realize the ideals of the co-operative is loaded with the ideal values . Way is a cultivated man, building businesses, and community development organization forming a co-operative institutional identity in implentasinya. Changes in the quality of co-operative organizations (people, organizations ,businesses,)as a result of empowerment is to realize the ideals of the co-operative as a pillar of the economy. Co-operative empowerment is a process to enable co-operative mengaktualisakan his identity, so it can perform the role of co-operatives in accordance with his mission to lead to the achievement of its objectives. About the scope of activities related to the empowerment of co-operatives. Include aspects of organizational and business aspects, can be developed into five aspects: aspects of ideology, organization, capital, management and business. While the participation of members of the co-operative is one form of participation in the co-operative members. Understanding of co-operative identity can be stated that the member has a central position, which is a source of strength to function as an initiator, controller, leader and also as a user of the continuity of life co-operatives. This means thatthe key to empowerment and the first major co-operative lies in the hands of members. From the viewpoint of strategic management into the 21st century vision ofthe co-operative is actualization of identity in the development through the empowerment of individual to achieveÂ the figure of a healthy cooperative, tough and independent